Evidence of promising biological-pharmacological activities of the sertraline-based copper complex: (SerH2)2[CuCl4] - Martini, Nancy (2017)
In the current study the ability of copper complex to exert multiple biological activities is combined with the pharmacological action of sertraline (SerH2Cl, antidepressant drug). The hydrated and anhydrous forms of the tetrachlorocuprate(II) salts, namely (SerH2)2[CuCl4]·½H2O and (SerH2)2[CuCl4], were synthesized and characterized by physicochemical methods. The crystal structures were determined by X-ray diffraction methods. The hydrate complex crystallizes in the monoclinic P21 space group with a =8.0807(2) Å, b =36.2781(8) Å, c =12.6576(3) Å, β =95.665(2)°, and Z =4 molecules per unit cell and the un-hydrate in P21 with a =13.8727(6) Å, b =7.5090(3) Å, c= 18.618(1) Å, β =104.563(6)°, and Z =2. It has been suggested that Cu(II) ions might be critical in the development of mood disorders, showed potent biocidal activity, and also acted as analgesic adjuvant. To improve sertraline efficiency, the antidepressant and analgesic activities of the complex have been assessed in rats denoting a marked synergistic effect. Antithyroid and antimicrobial activities were also evaluated. Because depressive disorders and hyperthyroidism diseases led to an oxidative stress state, antioxidant capability has also been tested. The complex behaved as a good superoxide radical scavenger (IC50=6.3 × 10−6 M). The ability of the complex to act as bromoperoxidase mimic was assessed. A pseudofirst order constant of k = 0.157 ± 0.007 min−1 has been determined. The complex evidences promising biological-pharmacological activities and the albumin binding studies showed a Kb of 2.90 ×103 M−1 showing an improvement in the uptake of sertraline by albumin at 8 h incubation (time required for effective interaction of sertraline with the protein).